2015
DOI: 10.1371/journal.pntd.0003536
|View full text |Cite
|
Sign up to set email alerts
|

Inter-epidemic Acquisition of Rift Valley Fever Virus in Humans in Tanzania

Abstract: BackgroundIn East Africa, epidemics of Rift Valley fever (RVF) occur in cycles of 5–15 years following unusually high rainfall. RVF transmission during inter-epidemic periods (IEP) generally passes undetected in absence of surveillance in mammalian hosts and vectors. We studied IEP transmission of RVF and evaluated the demographic, behavioural, occupational and spatial determinants of past RVF infection.MethodologyBetween March and August 2012 we collected blood samples, and administered a risk factor question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
2
35
0
Order By: Relevance
“…Previous studies have detected RVFV seropositivity among domestic and wild animals during long IEPs in southern Africa and other parts of east Africa, with seroprevalences ranging between 15% and 23% (Anderson & Rowe, ; Evans et al., ; Lichoti et al., ; Sumaye et al., ). Similarly, two studies on human hosts in east Africa detected RVF seroprevalences of between 11% and 13% (LaBeaud et al., ; Sumaye et al., ). Most of these earlier studies were seroprevalence studies carried out within one local ecosystem and did not actually observe seroconversions.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies have detected RVFV seropositivity among domestic and wild animals during long IEPs in southern Africa and other parts of east Africa, with seroprevalences ranging between 15% and 23% (Anderson & Rowe, ; Evans et al., ; Lichoti et al., ; Sumaye et al., ). Similarly, two studies on human hosts in east Africa detected RVF seroprevalences of between 11% and 13% (LaBeaud et al., ; Sumaye et al., ). Most of these earlier studies were seroprevalence studies carried out within one local ecosystem and did not actually observe seroconversions.…”
Section: Discussionmentioning
confidence: 86%
“…The hazard ratio for RVFV seroconversion was 0.71 (CI = 0.26-1.91, p = .11). Sumaye et al, 2015). Most of these earlier studies were seroprevalence studies carried out within one local ecosystem and did not actually observe seroconversions.…”
Section: Female Animals In Bura Irrigation Scheme and Husingo Villagementioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge this is the first investigation of RVFV among febrile patients in Mozambique and we found that 5 % (10/200) of febrile patients seroconverted to IgG antibodies against RVFV between their acute and convalescent samples. Although novel for Mozambique, this finding is not surprising, based on the following arguments: i) A recent study conducted by our group in the same area showed that Aedes mosquitoes were abundant [ 22 ] ii) recent studies conducted in several districts in the surroundings of the study area found elevated frequencies of anti-RVFV IgG antibodies in cattle [ 10 , 11 ], iii) several outbreaks and sporadic cases have been reported in countries neighboring Mozambique such as South Africa and Tanzania [ 4 , 8 , 23 ], iv) patients were recruited during and after the severe heavy rainfalls that occurred in southern Mozambique in 2013 [ 8 , 15 ], v) people living in the study area travel regularly to the surroundings districts where elevated frequencies of antibodies were recently documented in cattle [ 10 , 11 ] and vi) cattle population is much more frequent than sheep in the study area [ 24 ]. Although the source of infection was not investigated in this study, the fact that most of cases occurred between February through May, peaking in April, suggest that heavy rainfall and floods that occurred in the same period might have influenced the occurrence of RVFV in Mozambique.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic filariasis remains endemic in the country [ 20 ] and dengue fever viruses resulted in 1017 cases and 4 deaths in 2014 [ 21 ]. Other mosquito-borne infections such as Rift Valley fever [ 22 24 ] and Chikungunya have also been documented in some areas [ 25 27 ]. Ongoing mosquito control interventions such as long-lasting insecticidal nets (LLINs) and indoor spraying with residual insecticides (IRS) are having significant impact already [ 28 ], but the remaining residual transmission which occurs in spatially segregated areas must also be targeted to ensure elimination is achieved [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%